Floristic composition and plant cover in Yozgat rangelands, central Turkey - Dogrusoz M.C.; Mut H.; Basaran U.; Gulumser E.; Katlan E. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
This research was conducted to determine floristic compositions and plant cover area in four different rangelands of Yozgat province located in central Turkey. The observations and measurements were carried out in Koccagiz village of Sarikaya district, Taspinar village of Sorgun district, Hacilar and Kordeve district of Yerkoy in May 2014. Investigated rangelands are open to graze. Vegetation measurements sampling in rangelands were performed by using Loop method. Total 34 different plant species were determined in vegetation survey. Plant cover area in Koccagiz, Taspinar, Hacilar and Kordeve district was determined 60.6%, 66.5%, 55.0% and 44.9%, respectively. Over the rangelends, the ratio of legumes, grasses and other families in floristic composition respectively varied between 6.4 and 22.0%, 41.0 and 79.1%, 14.5 and 49.1%. In addition the ratio of decreaser, increaser and invader plant in floristic composition varied from 2.9 to 18.2%, 41.0 to 65.4%, 16.4 – 55.0%, respectively in the investigated rangelands. Koccagiz rangeland was in poor class, other rangelands were in medium class.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)